The Tuupovaara end moraine in North Karelia, Eastern Finland - an ice-marginal formation of the same age as the Salpausselkä ridges - H. Rainio (Bulletin of the Geological Society of Finland, 1983)
Described in this report is a previously for the most part unknown ice-marginal formation in the province of North Karelia extending from the parish of Värtsilä via Tohmajärvi and Tuupovaara to the parish of Ilomantsi. The formation is given the name Tuupovaara End Moraine. Including a few short gaps, it is 50 kilometers long, trends N - S and SSW-NNE and runs at distances varying between 12 and 22 kilometers from the distal flank of Salpausselkä II. The parts formed in the Baltic Ice Lake and the local ice lake of Loitimo consist mainly of glaciofluvial material, while the supra-aquatic parts, again, are composed mostly of till and are much smaller than the glaciofluvial parts. The Tuupovaara End Moraine is slightly younger than Salpausselkä I, but distinctly older than Salpausselkä II. This indicates that the margin of the continental ice sheet did not extend during the formation of Salpausselkä I from Värtsilä to the ice-marginal formation between Kiihtelysvaara and Selkäkangas, and that the ice receded more rapidly in the Ilomantsi area than elsewhere. The esker complex of Otmen, which is located on the east side of the Tuupovaara End Moraine at a distance of between two and five kilometers, rests on the boundary between two different sets of striations. Judged on this evidence and by its structural features, it must be identified as an interlobate complex.